Vous êtes sur la page 1sur 3

MA 102 (Ordinary Differential Equations)

IIT Guwahati
Tutorial Sheet No. 2 Date: March 15, 2018

Exact differential equations; Integrating Factors; Higher-order linear IVPs; Wronskian.

(1) Under what conditions, the following differential equations are exact?
(a) (ax + by)dx + (kx + ly)dy = 0; (b) [f (x) + g(y)]dx + [h(x) + l(y)]dy = 0;
(c) (x3 + xy 2 )dx + (ax2 y + bxy 2 )dy = 0.

Solution: (a) b = k; (b) g 0 (y) = h0 (x); (c) a = 1, b = 0;

(2) Are the following equations exact? If exact, obtain the general solution.
(a) (2xy − sec2 x)dx + (x2 + 2y)dy = 0. (b) (x − 2xy + ey )dx + (y − x2 + xey )dy = 0.

Solution: (a) Since My (x, y) = 2x = Nx (x, y), the equation is exact. Then, there exists f (x, y)
such that fx = M and fy = N . Integrate fx = M w.r.t. x to have
Z
f (x, y) = (2xy − sec2 x)dx + g(y) = x2 y − tan x + g(y).

Now, x2 + 2y = fy (x, y) = N (x, y) = x2 + 2y =⇒ g 0 (y) = 2y. Thus, g(y) = y 2 . Hence, the


solution to the equation is given implicitly by f (x, y) = c i.e., x2 y − tan x + y 2 = c.

(b) In this case, My = −2x + ey = Nx . Arguing as in (a), we obtain

x2
Z
f (x, y) = (x − 2xy + ey )dx + g(y) = − x2 y + xey + g(y).
2
and g(y) = y 2 /2.
x2
The general solution is thus given by f (x, y) = c i.e., 2 − x2 y + xey + y 2 /2 = c.

(3) In each case find an integrating factor and solve:


(a) y 0 − (2/x)y = x2 cos x, (b) ydx + (x2 y − x)dy = 0, (c) y(2x2 y 3 + 3)dx + x(x2 y 3 − 1)dy = 0
R R
Solution: (a) I.F. µ(x) = e p(x)dx = e −(2/x)dx = x−2 . Multiplying by µ(x) = x−2 yields
d −2 2 2
dx (x y) = cos x. Integrating and solving for y, we obtain y(x) = x sin x + Cx .
R
(b) Note that (My − Nx )/N = −(2/x). I.F. µ(x) = e −(2/x)dx = x−2 . The general solution is
1 2 y
2 y − x = C where x 6= 0.

(c) My = 8x2 y 3 + 3 6= Nx = 3x2 y 3 − 1. Multiplying the equation throughout by xa y b , we have

(2xa+2 y b+4 + 3xa y b+1 )dx + (xa+3 y b+3 − xa+1 y b )dy = 0.

The exactness condition leads to

2(b + 4)xa+2 y b+3 + (b + 1)3xa y b = (a + 3)xa+2 y b+3 − (a + 1)xa y b .

Divide both sides by xa y b , we obtain 2b + 8 = a + 3, 3b + 3 = −a − 1 =⇒ a = 7/5, b = −9/5.


Thus, I.F. is x7/5 y −9/5 .
2

(4) Show that if (Nx − My )/(xM − yM ) = g(xy) then the equation M (x, y)dx + N (x, y)dy = 0 has
R 
an integrating factor of the form µ(xy), where µ(u) = exp g(u)du .

Solution: Note that


Z  Z 0
0
µ (u) = exp g(u)du g(u)du = µ(u)g(u).

Since µ(xy)M dx + µ(xy)N dy = 0 is exact, we have


∂ ∂(xy)
{µ(xy)M } = µ0 (xy) M + µ(xy)My
∂y ∂y
= µ(xy) [g(xy)xM + My ] ,

∂ ∂(xy)
{µ(xy)N } = µ0 (xy) N + µ(xy)Nx
∂x ∂x
= µ(xy) [g(xy)yN + Nx ] .
Now, (Nx − My ) = (xM − yN )g(xy) =⇒ yN g(xy) + Nx = xM g(xy) + My , hence
∂ ∂
{µ(xy)M } = {µ(xy)N }.
∂y ∂x
(5) Find the particular solution of
(a) xy 0 + 3y = sin
x2
x
, x 6= 0, y(π/2) = 1.

0 2, 0 ≤ x < 1,
(b) y + y = f (x), y(0) = 0, where f (x) =
0, x ≥ 1.
y3
(c) x2 y 0 + xy = x, y(1) = 1, x 6= 0.

Solution: (a) I.F. µ(x) = x3 . The general solution is x3 y(x) = − cos x+C. The initial condition
3 3
y(π/2) = 1 =⇒ C = π8 . The particular solution is yx3 + cos x = π8 .

(b) Split the problem into two IVPs: I. For 0 ≤ x < 1, y 0 + y = 2, y(0) = 0;
II. For x ≥ 1, y 0 + y = 0, y(1) = k, where limx→1− φ1 (x) = k, and φ1 (x) is the solution of I. The
solution of IVP I is φ1 (x) = 2 − 2e−x . Now,
lim φ1 (x) = lim (2 − 2e−x ) = 2 − 2e−1 = k.
x→1− x→1−

This value k = 2 − 2e−1


would be the initial condition for IVP II. The solution of IVP II is
−x
φ2 (x) = (2e − 2)e for x ≥ 1. The solution of the given IVP is
φ1 (x) = 2 − 2e−x ,

0 ≤ x < 1,
y(x) =
φ2 (x) = (2e − 2)e−x , x ≥ 1.
(c) Multiplying both sides of the equation by y −3 and substituting v(x) = y −2 transform into
−2
a linear equation v 0 − (2/x)v = −(2/x3 ). Its general solution is v(x) = x 2 + Cx2 . Replacing
−2 2
v = y −2 , we obtain y −2 = x 2 + Cx2 . Using IC y(1) = 1, we obtain y 2 = x2x
4 +1 .

dy
(6) Given that y1 (x) = x is a solution of = −y 2 + xy + 1, obtain the general solution.
dx

Solution: This is a Riccati equation with one solution f (x) = x is known. The substitution
1
y(x) = f (x) + v(x) = x + v1 transforms the given equation to a linear equation in v(x), i.e.,
−x2 /2 v(x) =
dv
R −x2 /2
dx − xv = 1. Its solution is e e dx + C. Now, replacing v(x) = 1/(y(x) − x), we
obtain
2
e−x /2
Z
2
= e−x /2 dx + C.
y−x
3